(untitled) (BIRDEM Medical Journal, 2021)
Background: Well controlled blood pressure (BP) is associated with decreased risk of kidney disease progression, cardiovascular events and death. Patients with chronic kidney disease (CKD) are frequently seen to have low rates of BP control. This study aimed to find out the proportion of adult type 2 diabetic CKD patients with hypertension achieving the goal of target blood pressure. Methods: This cross-sectional study included 105 hypertensive subjects having type 2 diabetes and CKD at the outpatient department of Nephrology, BIRDEM General Hospital in Dhaka, Bangladesh from May to August, 2012. Results: The mean age was 55.6 years and maximum numbers of patients were in the age group of 39-66 years. Among 105 subjects, 52.3% were male and rest 47.7% were female. The mean duration of diabetes, CKD and hypertension were 6.73 (±3.22), 3.12 (±2.47) and 3.1 (±1.77) years respectively. The study revealed that ischemic heart disease (30.5%), dyslipidemia (56.1%) and stroke (13.3%) were associated comorbidity along with diabetes and CKD. Mean estimated glomerular filtration rate was 52.19 ml/min. Mean serum creatinine level was 3.4 mg/ dl. It was observed that majority (49.5%) of the study subjects were prescribed at least two drugs to control hypertension. Three anti-hypertensive medications were given in 35.2% subjects. Among 105 study subjects, 25.7% were found to have high systolic blood pressure and 8.8% high diastolic blood pressure. It was observed that only 40% subjects achieved target systolic blood pressure and 68.6% reached the target diastolic pressure for CKD with diabetes. In correlation analysis, it was observed that both systolic and diastolic blood pressure was significantly correlated with age of the subject, duration diabetes and duration of HTN. Conclusion: From the present study it was seen that both the target systolic and diastolic blood pressure were correlated with numbers of medications used for controlling hypertension but only diastolic blood pressure control was significantly correlated with number of medication used in this present study. BIRDEM Med J 2021; 11(3): 212-217